The Adoption of Public-Private Partnership Concessions for a Development Project in Emerging Economies - Viktor Suryan; Pintanugra Persadanta; M Dimas Bara Alddi; Jhellyananda Putri (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2020)
Public-private partnership define as a corporation between public as owner and private as manager and operational. This paper aims to describe the PPP development in infrastructure project in emerging economies. The result show the implementation of PPP conducted are based on the principle of a fair, open, transparent, and competitive. Also, the activities of Public-Private Partnership are important for all parties to understand each other, mission, functions and duties, rights, obligations of each as agents of development. It also do perception in the negotiation of partnership activities which is needed transparency, the commitment of development actors to the achievement of results mutual benefit. In addition, the need for the direct involvement of all parties, especially local government, parliament, the public, employees and others, the availability and access relevant data, easily, correctly and consistently. Hence, support for a clear and true to good decision giving the Central , Provincial or Regional (district or city ), auction eligibility criteria and negotiation clearly, transparent and consistent, and ability in mastering the material law, technical and finance.